Androgen receptor‐related micro RNAs in prostate cancer and their role in antiandrogen drug resistance. Issue 4 (10th October 2019) - Rezaei, Samaneh; Mahjoubin Tehran, Maryam; Sahebkar, Amirhossein; Jalili, Amin; Aghaee‐Bakhtiari, Seyed Hamid
Abstract: Prostate cancer (PCa) is one of the most common cancers and the fifth most common reason for cancer deaths in the males. Surgical castration combined with androgen deprivation therapy, antiandrogens, and androgen synthesis inhibitors is the current therapeutic modalities for PCa. These strategies inhibit androgen synthesis or reduce its binding to the androgen receptor (AR) but the development of resistance to these therapies and transient responsiveness are challenging issues in the treatment of this cancer. Deregulation of ARs has a vital role in the initiation and progression of PCa. Also, recent findings imply that micro RNAs (miRNAs) are involved in the evolution of PCa and mediate drug resistance in different cancers. Hence, discovering and targeting miRNAs might represent a novel therapeutic approach. This review paid particular attention to the AR pathway and existing information on the possible roles of miRNAs associated with AR pathway and drug resistance to two second‐generation antiandrogens, that is, enzalutamide and abiraterone. Abstract : Micro RNAs (miRNAs) are involved in the evolution of prostate cancer and mediate drug resistance in different cancers. Discovering and targeting miRNAs might represent a novel therapeutic approach. This review paid particular attention to the androgen receptor (AR) pathway and existing information on the possible roles of miRNAs associated with AR pathway and drug resistance.